Synthesis of 14-Substituted-14H-dibenzo[a,j]xanthenes under Solvent-Free Conditions Presence of Etidronic Acid - Wu, Liqiang; Ma, Weiwei; Yang, Limin; Yan, Fulin (Asian Journal of Chemistry, 2010)
A simple and efficient synthesis of 14-substituted-14 H-dibenzo[a,j]-xanthenes has been accomplished by the one-pot condensation of b-naphthol and aldehyde under solvent-free conditions in the presence of etidronic acid.